Design of Micro-strip Symmetrical Dual-band Filter Based on Wireless Sensor Network Nodes - Wenbo Cheng; Kai Deng; Wei Cheng (EURASIP Journal on Wireless Communications and Networking, 2019)
Abstract The micro-strip antenna filter design of wireless sensor network nodes is usually used to improve the out-of-band suppression and frequency selectivity by increasing the order of the filters, but the filters are usually single band, not only the size is large, but also the in-band characteristics of the filters are not ideal. This paper proposes a method to design a micro-strip symmetric dual-band filter in wireless sensor network nodes. Firstly, the coupling matrix of single-passband filter is obtained by using the synthesis method of generalized Chebyshev filter function. Then, the coupling matrix of the dual-passband filter is generated according to the reflection zeros and the transmission zeros. Finally, the S parameters response curve is drawn by mapping the normalized frequency domain of the dual-passband to the actual frequency domain. According to the data analysis and experimental results, the method is feasible and effective to design a micro-strip symmetrical dual-band filter. It can not only provide a more guiding design method for the joint design of antenna and RF front-end circuit, but also realize the spread of single-passband filter to multi-frequency for a wireless sensor network node antenna.